Role of Women in Crop Residue Management for Better Health - Jat, Mangi Lal; Rana, Meenakshy; Bijarniya, Deepak; Kalvaniya, Kailash C.; Kumar, Yogesh; Rana, Dharamvir Singh (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The role of women has changed dramatically from stone age to contemporary global society. The process of Industrialization, modernization and globalization show its deep impact on human society all over the world. The role and responsibilities of women have attained new definition and perspective. On the encouraging side, in the Northwest India, there has been a relatively increase in economic participation in the past one decade. Development programmes and policies have largely tended to focus on women in isolation with little effort to work alongside men and include them in restructuring social relations to mainstream gender. If women’s empowerment is to be achieved and sustained in agriculture, it must be complemented by programmes that include working with men to bring about the desired structural change. The training workshop was conducted to motivate the women folks of Haryana villages to participate in the agricultural activities, support to bring change and updating in farming practices by adopting new trending mechanization and techniques like Happy Seeder, Green Seeker, Soil Humidity Meter, adopt techniques like ‘Lekha-Jhokha’ for better farming practices, and to earn profits by their contributions. The main focus was to make aware women to participate in no burning of rice crop residue, so that they can influence in reducing the air pollution and strengthen the Conservation Agriculture (CA), to enhance the field nutrients by sustainable agricultural practices.